2010
DOI: 10.1016/j.bios.2010.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of controlled polymeric cross-linked coatings via iniferter polymerisation in the presence of tetraethyl thiuram disulphide chain terminator

Abstract: A "grafting from" approach has been used for controlled deposition of cross-linked polymers by living radical polymerisation. Borosilicate glass was modified with N,N-diethylaminodithiocarbamoylpropyl(trimethoxy)silane, in order to confine the iniferter reactive groups solely at its surface, then placed in solution with monomers and cross-linker. The polymerisation was initiated by UV irradiation. Formation of the cross-linked polymers was studied in terms of time course of the reaction, type of monomers incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Porous silica particles (SiliCycle®) were from Teknokroma (Barcelona, Spain) whose average diameter, pore size and surface area were 10 μm, 10 nm and 432 m 2 g À1 respectively. The iniferter N, N ′-diethylaminodithiocarbamoylpropyl(trimethoxy)silane (DDCPTS) was synthesized as reported elsewhere (Bossi et al, 2010). Reagents required for its synthesis, that is sodium diethyl dithiocarbamate trihydrate and chloropropyl trimethoxysilane ≥97%, were obtained INIFERTER-MEDIATED GRAFTING OF MIP ON POROUS SILICA BEADS from Sigma-Aldrich (Madrid, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…Porous silica particles (SiliCycle®) were from Teknokroma (Barcelona, Spain) whose average diameter, pore size and surface area were 10 μm, 10 nm and 432 m 2 g À1 respectively. The iniferter N, N ′-diethylaminodithiocarbamoylpropyl(trimethoxy)silane (DDCPTS) was synthesized as reported elsewhere (Bossi et al, 2010). Reagents required for its synthesis, that is sodium diethyl dithiocarbamate trihydrate and chloropropyl trimethoxysilane ≥97%, were obtained INIFERTER-MEDIATED GRAFTING OF MIP ON POROUS SILICA BEADS from Sigma-Aldrich (Madrid, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…The first one is the formation of solid nanocore (seed particle) while the second stage is the grafting of the imprinted shell [107]. The solid core can be formed from diverse materials containing additional functionalities suitable for anchoring e.g., catalytic groups capable of initiating polymer grafting [108,109]. This approach allows formation of recognition sites at the surface of MIP beads [107,110] improving analyte transfer [111,112].…”
Section: Core-shell Grafting and Polymerizationmentioning
confidence: 99%
“…98 Together with MAA and EGDMA, An2 could be grafted from a modified glass surface. 99 For this purpose, borosilicate glass slides were modified with N,N-diethylaminodithiocarbamoylpropyl(trimethoxy)silane followed by subsequent polymerization using the iniferter polymerization technique. It was found that the N,N-tetraethyl thiuram disulphide chain terminator enhanced the control over the polymerization.…”
Section: Polymerizable Aromatic Dyesmentioning
confidence: 99%